The Relationship Between the Level of Knowledge and Adherence to Taking Medication for the Prevention of Hypertension - Dhuma Aza Alwintara; Supratman Supratman (Indonesian Journal of Global Health Research, 2024)
High blood pressure or hypertension is a condition where blood pressure always exceeds normal limits, with systolic blood pressure exceeding 140 mmHg and diastolic blood pressure exceeding 90 mmHg. The aim of this research is to identify whether there is a relationship between the level of knowledge and compliance in taking medication in elderly people who suffer from hypertension. This research applies a quantitative approach with a sample of 96 respondents, selected using a random sampling technique (random sampling). The data in this study were analyzed univariately and bivariately, by applying the Spearman test to assess the relationship between all the variables studied. Data collection was carried out using a questionnaire that measured the level of knowledge, namely, with the validity and reliability of Cronbach alpha values of 0.856 for 21 valid questions, and compliance with taking medication, namely, with the validity and reliability of Cronbach alpha values of 0.728 for 8 valid questions. Two questionnaires were used in this study: Compliance Level and MMAS 8. The results of the analysis of respondents' level of knowledge revealed that the majority of respondents had good knowledge, namely 66.7%, followed by sufficient knowledge at 30.2%, and insufficient knowledge at 3.1%. Meanwhile, for the level of compliance with taking medication, the majority of respondents were compliant (71.9%), followed by moderate (25.3%) and low (3.1%) levels of compliance.Reviewing the results of the Spearman Rank (Rho) statistical test, we obtained a value of 0.075 with a p-value = 0.05, which indicates that there is no significant relationship between the level of knowledge and compliance in taking medication.